Early Passive Leg Movement Prevents Against the Development of Heart Failure With Preserved Ejection Fraction in Rats - Liu, Jian; Ji, Xi-xin; Fu, Yang; Zhang, Wen-chao; Ji, Hui-fang; Liu, Jian-wei; Cheng, Xiao-shu; Dong, Yi-Fei (Frontiers in Cardiovascular Medicine, 2021)
Exercising was reported by several studies to bring great benefits to heart failure with preserved ejection fraction (HFpEF), which reduced the hospitalization and the mortality of heart failure. However, the underlying mechanism of exercising on HFpEF remains unclear. In the present study, we designed and constructed a device that can perform early passive leg movement (ePLM) in rats and further observed whether treatment of ePLM exerts protective effects on HFpEF of rats. Rats were fed with high salt feed to establish an animal model of pre-clinical diastolic dysfunction (PDD), which would eventually develop into HFpEF, and then treated rats with ePLM. We conducted several experiments to evaluate the conditions of heart and blood vessel. The results show that diastolic functions of heart and blood vessel in rats were significantly improved by treatment of ePLM. We also found that pathological injuries of heart and blood vessel were ameliorated after treatment of ePLM. Moreover, treatment of ePLM decreased the protein levels of Collagen type I, Collagen type III, MMP2, and MMP9 in heart and blood vessel, indicating that cardiac and vascular fibrosis were reduced apparently by treatment of ePLM. Further investigation suggested that treatment of ePLM probably inhibit the activation of TGF-β1/Smad3 signaling pathway as well as promote the activation of Akt/eNOS signaling pathway in high salt diet induced HFpEF. In conclusion, treatment of ePLM alleviated high salt diet induced HFpEF by inhibiting fibrosis via suppressing TGF-β1/Smad3 signaling pathway as well as activating Akt/eNOS signaling pathway, implicating treatment of ePLM as a promising novel non-pharmacological approach for HFpEF.